"It's Created by a Community": Local Context Mediating Districts' Approaches to Serving Immigrant and Refugee Newcomers. (July 2021) - Hopkins, Megan; Weddle, Hayley; Bjorklund, Peter; Umansky, Ilana M.; Blanca Dabach, Dafney
Literature examining the context of reception reveals how various structural and cultural factors shape newcomers' experiences, and thus their opportunities for integration. Fewer studies explore how school districts are situated in this broader context of reception, or how district policies and practices for newcomers are enabled or constrained by the local context. This study draws on a zones of mediation framework to examine how external forces mediated districts' approaches to serving growing numbers of immigrant and refugee newcomers. Analysis of interviews with 57 stakeholders from across three districts revealed that the presence or absence of community-based support networks, as well as the extent to which local policies and perceptions emphasized inclusion, mediated districts' programmatic approaches. Implications for district and community leaders are discussed.